The effect of dwelling-based and neighbourhood-based precariousness on mental wellbeing - Hewton, Jack; Ong ViforJ, Rachel; Singh, Ranjodh (2023)
This study examines the impacts of dwelling-based and neighbourhood-based precariousness on mental wellbeing by applying panel data modelling approaches to the 2001–2020 Household, Income and Labour Dynamics in Australia (HILDA) survey. We find that living in unaffordable housing has the largest adverse effects on mental wellbeing among all forms of dwelling-based precariousness modelled in the study. Neighbourhood hostility and neighbourhood crime are key forms of neighbourhood-based precariousness that depress mental wellbeing. On the other hand, some forms of housing precariousness have insignificant impacts on wellbeing, in particular overcrowding and vandalism. Notwithstanding the importance of neighbourhood aspects, overall dwelling-based precariousness has a larger detrimental impact on mental wellbeing than neighbourhood-based precariousness. We test the robustness of linear models by implementing Tobit models that take into account the bounded nature of wellbeing measures that are ignored in linear models. We find that both models produce similar findings. The analysis in this study leads to important policy implications in a world that is increasingly exposed to public health crises. Importantly, the findings point to an urgency for policies and programs to be embedded within housing systems that ensure vulnerable population groups have long-term rather than temporary access to secure housing.